2021
DOI: 10.3390/ma14143841
|View full text |Cite
|
Sign up to set email alerts
|

Peening Techniques for Surface Modification: Processes, Properties, and Applications

Abstract: Surface modification methods have been applied to metals and alloys to change the surface integrity, obtain superior mechanical properties, and improve service life irrespective of the field of application. In this review paper, current state-of-the-art of peening techniques are demonstrated. More specifically, classical and advanced shot peening (SP), ultrasonic impact peening (UIP), and laser shock peening (LSP) have been discussed. The effect of these techniques on mechanical properties, such as hardness, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 168 publications
0
20
0
Order By: Relevance
“…Moreover, only a few studies have been carried out on the addition of solid lubricants and strengthening phases in the HEAs matrix. There is still a broad scope to study and create a guideline to choose suitable solid lubricants in HEAs to control COF as the solid lubricants have multiple categories [ 77 ]. Future studies can be focused on the distribution of solid lubricants in HEAs without reacting with the initial metal constituents.…”
Section: Future Scope Of the Heas For Tribological Applicationsmentioning
confidence: 99%
“…Moreover, only a few studies have been carried out on the addition of solid lubricants and strengthening phases in the HEAs matrix. There is still a broad scope to study and create a guideline to choose suitable solid lubricants in HEAs to control COF as the solid lubricants have multiple categories [ 77 ]. Future studies can be focused on the distribution of solid lubricants in HEAs without reacting with the initial metal constituents.…”
Section: Future Scope Of the Heas For Tribological Applicationsmentioning
confidence: 99%
“…Corrosion is detrimental to material life cycle and therefore coating is often used to reduce corrosion. Metals, especially different kinds of steels, are prone to corrosion [147]. EAP coatings are particularly effective to prevent corrosion on cold-rolled steel (CRS) [148].…”
Section: (B) Corrosion Reductionmentioning
confidence: 99%
“…Surface strengthening by different severe plastic deformation (SPD) methods has been widely perceived to enhance surface mechanical properties [1]. Researchers have used SPD by shot peening [2,3], severe shot peening (SSP) [4,5], ultrasonic impact peening [6,7], ultrasonic shot peening (USP) [8,9], laser shock peening [10,11], direct and indirect laser shock surface patterning (LSSP) [12,13], surface mechanical attrition treatment (SMAT) [14,15], and deep cold rolling (DCR) [16]. These surface SPD techniques could induce residual compressive stress (RCS) and closure of existing microcracks and microcavities on the surface [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…There are significant reviews on various surface SPD methods to enhance surface integrity and surface mechanical properties. John et al [10] comprehensively reviewed the three most commonly used peening techniques such as SP, UIP, and LSP for a broad range of engineering materials and elucidated the influence of various process parameters on surface mechanical properties. Their study revealed superior enhancement in surface There are significant reviews on various surface SPD methods to enhance surface integrity and surface mechanical properties.…”
Section: Introductionmentioning
confidence: 99%